Union with God: Cross Textual Reading in Surat Centhini VI and John 15: 1-8 - Antonius Galih Arga Wiwin Aryanto; Albertus Lilik Kurniawan (Litbang STFT Widya Sasana Malang, 2023)
The article wants to analyze the meaning of “union with God” in Javanese literature, Surat Centhini and in the Christian bible, John 15: 1-8. John Gospel has one focuses on the need of human beings to have a deep relationship with God. the same idea also can be found in Javanesse text, Surat Centhini. Both has the same purpose of spiritual life that is union with God or manunggaling kawula Gusti. The methodology will employ